The Role of Sleepiness on Arterial Stiffness Improvement After CPAP Therapy in Males With Obstructive Sleep Apnea: a Prospective Cohort Study - Mineiro, A (2017)
BACKGROUND: Obstructive sleep apnea (OSA) is associated with increased cardiovascular risk. This study aim to assess differences in changes in arterial stiffness of two groups of patients, defined as having daytime sleepiness or not, after continuous positive airway pressure (CPAP) treatment. METHODS: A selected cohort of consecutive male patients, under 65 years old, with moderate to severe OSA and without great number of comorbidities was studied. The diagnosis was confirmed by home respiratory poligraphy. Sleepiness was considered with an Epworth Sleepiness Scale (ESS) > 10. An ambulatory blood pressure (BP) monitoring and carotid-femoral pulse wave velocity (cf-PWV) measurements were performed, before and after four months under CPAP. Compliant patients, sleepy and non-sleepy, were compared using linear mixed effects regression models. A further stratified analysis was performed with non-sleepy patients. RESULTS: Thirty-four patients were recruited, with mean age 55.2 (7.9) years, 38.2% were sleepy, 79.4% with hypertension, 61.8% with metabolic syndrome and 82.4% with dyslipidaemia. In univariable analysis, cf-PWV was strongly related to systolic BP parameters and age, but also to antihypertensive drugs (p = 0.030), metabolic syndrome (p = 0.025) and daytime sleepiness (p = 0.004). Sleepy patients had a more severe OSA, with AHI 44.8 (19.0) vs 29.7 (15.7) events/h (p = 0.018), but sleep study parameters were not associated with cf-PWV values. On multivariable regression, a significant interaction between time (CPAP) and sleepiness (p = 0.033) was found. There was a weak evidence of a cf-PWV reduction after CPAP treatment (p = 0.086), but the effects of treatment differed significantly between groups, with no changes in non-sleepy patients, while in sleepy patients a significant decrease was observed (p = 0.012). Evaluating non-sleepy patients group under CPAP therapy, results showed that both higher pulse pressure (p = 0.001) and lower LDL-cholesterol levels (p = 0.015) at baseline were associated to higher cf-PWV changes. CONCLUSIONS: Patients with daytime sleepiness had a more severe OSA and presented a greater arterial stiffness improvement after CPAP therapy, independently from age and BP. Besides sleepiness, cf-PWV reduction after CPAP therapy was mainly associated to CV risk factors, and less to sleep study parameters.